STRATEGI INTEGRATIF SENI KONTEMPORER DALAM PENDIDIKAN KRISTEN MASA KINI - Samben, Daniel Ruppa (JURNAL POKOK ANGGUR, 2024)
This article provides an in-depth discussion of the role of contemporary art in Christian education in the modern era, which is characterized by rapid cultural and technological changes. Contemporary art, with its innovative, experimental, and often interdisciplinary nature, presents both opportunities and challenges for Christian education in maintaining its relevance amidst ongoing societal transformations. Christian education faces the need to harmonize timeless faith-based values with the ever-evolving creative expressions of younger generations. In this context, contemporary art functions not only as an aesthetic medium but also as a means of learning, strengthening faith identity, conveying moral values, and fostering deep spiritual reflection. This article examines the definition and characteristics of contemporary art, explores its relevance to Christian education, and analyzes contextual and effective strategies for its integration. The approaches discussed include the utilization of new media, the enhancement of student participation, and interdisciplinary collaboration to enrich the learning experience. Through this analysis, it is expected that Christian education can maximize the potential of contemporary art as a bridge between faith-based values and current cultural realities, thereby nurturing a generation that is creative, critical, and firmly rooted in Christian principles amidst global challenges.